2008
DOI: 10.1038/sj.jp.7211924
|View full text |Cite
|
Sign up to set email alerts
|

Sucking and swallowing in infants and diagnostic tools

Abstract: Preterm infants often have difficulties in learning how to suckle from the breast or how to drink from a bottle. As yet, it is unclear whether this is part of their prematurity or whether it is caused by neurological problems. Is it possible to decide on the basis of how an infant learns to suckle or drink whether it needs help and if so, what kind of help? In addition, can any predictions be made regarding the relationship between these difficulties and later neurodevelopmental outcome? We searched the litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0
19

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(88 citation statements)
references
References 46 publications
2
67
0
19
Order By: Relevance
“…23 SP da Costa et al study mentioned that it is unclear whether poor suckling is part of their prematurity or whether it is caused by neurological problems. 24 Present study indicates that a mostly (80%) of multiparous mothers had good position and attachment, which could be the outcome of their earlier practice. Fazlur Rahim et al reported that Primiparas women were poorer in Position (64% against 38.5%), Bonding (50% against 22%), and suckling (59% against 22%) in comparison to multiparas.…”
Section: Discussionmentioning
confidence: 81%
“…23 SP da Costa et al study mentioned that it is unclear whether poor suckling is part of their prematurity or whether it is caused by neurological problems. 24 Present study indicates that a mostly (80%) of multiparous mothers had good position and attachment, which could be the outcome of their earlier practice. Fazlur Rahim et al reported that Primiparas women were poorer in Position (64% against 38.5%), Bonding (50% against 22%), and suckling (59% against 22%) in comparison to multiparas.…”
Section: Discussionmentioning
confidence: 81%
“…Safe, effective and efficient swallowing throughout development relies on intricate sensory development, fine motor coordination of the swallowing musculature, and maturation of feeding skills to ensure airway protection and full bolus clearance from the oropharyngeal segment (1)(2)(3). Physiologically, pressure changes across the pharyngo-esophageal segment drive bolus movement during the swallowing process.…”
Section: Introductionmentioning
confidence: 99%
“…Ketidakmampuan minum pada bayi prematur disebabkan oleh kemampuan otot mengisapmengisap masih lemah, kapasitas oral belum stabil, dan penyebab yang berhubungan dengan gangguan neurologi. Keefektifan koordinasi antara refleks mengisap, menelan, dan bernapas pada bayi prematur dipengaruhi oleh kematangan struktur otak dan saraf kranial (Da Costa, van den Engel-Hoek, & Bos, 2008;Glass & Wolf, 1994).…”
Section: Pendahuluanunclassified